FEEDBACK AND SELF REGULATION IN WRITING LEARNING ASSESMENT IN JUNIOR HIGH SCHOOL - Titik Harsiati (Jurusan Sastra Indonesia, 2017)
This article aims to analyze the pattern of feedback and self-regulation in writing assessment in junior high school. The feedback in the writing assessment in junior high school is done quantitatively in the form of a score in the final product. Self-regulation in the assessmentas a learning tool is done in the form of reflections on competencies that have been mastered and have not been mastered. The implementation of feedback and self-regulation in the learningassessment in junior high school is not suitable yet in terms of reversal principle and self-regulation in the context of assessment as a learning tool.